PENGARUH PENGALAMAN AUDIT, SKEPTISME PROFESIONAL, RED FLAGS, DAN TEKANAN ANGGARAN WAKTU TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (Studi Empiris pada Kantor Akuntan Publik di DKI Jakarta) - Arsendy, Muhammad Teguh; Anugerah, Rita; Diyanto, Volta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study was aimed to examine the influence of audit experience, professional skepticism, red flags , and time budget presure to the ability auditor in detecting fraud. The population of this study are auditors who worked on the Public Accounting Firms (KAP) and listed on the Directory Indonesian Institute of Certified Public Accountants (IAPI) 2016 in DKI Jakarta. The samples of the study are all companies were selected by convenience sampling method. 44 auditor who worked on 10 KAP were chosen as the samples of this study. This study used multiple linear regression analysis was used to test whether the independent variables affect the dependent variable. Data analysis for hypothesis test was done with Statistical Package for the Social Sciences (SPSS) ver. 16. Results of regression testing (t-test) showed that the audit experience, professional skepticism, red flags , and time budget presure have a significant relationship with the ability auditor in detecting fraud on Public Accounting Firm (KAP) in DKI Jakarta. The amount of R Square (R2) of 0,708 gives the sense that the rate of 70,8% ability auditor in detecting fraud can be explained by the independency, competence, knowledge to detect errors, and time budget pressure while 29,2% can be explained by other variables.Keywords :Experience, Skepticism, Redflags, Time, and Fraud.